IN WORKS OF AZOUZ BEGAG"LAUGHING CORRECTS MORALS" - Zid, Mahdi (Journal of Human Sciences, 2021)
"Castigat ridendo mores" or correcting men by entertaining them said Molière in Tartuffe’s preface: It is from this principle that this article was written to show to what extent this process is used by Azouz Begag in the writing of his novels, in the aim to focus on some mentalities and practices that exist in Algeria or in France and that may prevent both nations from understanding each other. Using humour as a writing strategy with Begag is a result of his own personality or may it be a sort of pretence to reduce the emotional charge that characterizes this kind of writing or novels called "beurs".